Technical advantages of the city sedimentation water reconstruction system - Donenko, V. I.; Nazarenko, O. M.; Nazarenko, I. A.; Marchenko, M. P.; Sulima, V. P. (Ways to Improve Construction Efficiency, 2020)
The work designs a system of production components of urban infrastructure to create an energy efficient city. Hydraulic, hydrological, heat exchange processes of interaction of water structure and elements of treatment structures for centrifugal deposition of suspended matter have been investigated. Depending on the degree of contamination, devices for resource recovery are calculated. The duration of recovery operations was investigated. The technological cycle of re-water recovery and the number of cycles of cavitation generator for controlled conditioning of conditionally clean and dirty waters have been determined. Reverse osmosis devices for the recovery of conditionally pure water have been investigated. Categorized potential effluents of industrial waters as appropriate for restoration. Samples of experimental sediments for the needs of the construction industry at operating and supercritical modes of operation of the technological stream were obtained. A mathematical model of the productivity of irrigation of agro-centers in drought conditions with drip irrigation by repeated water has been developed.